Inclusión educativa y su influencia en el desarrollo de habilidades socioafectivas de los niños de Inicial II - Izurieta Angulo, María Mercedes (2025)
Educational inclusion is a fundamental element in the optimal development of students, since it promotes respect for social and individual differences, allowing the student to be able to function on their own within their own environment while taking into consideration their feelings and emotions. Therefore, within the Emigdio Esparza Moreno Educational Unit, specifically in sublevel II. It was observed that, in said sublevel, there are children who do not have good emotional communication with others, since it is difficult for them to relate and participate in group activities given their different abilities, making the lack of development of educational inclusion in the institution evident. As part of the research methodology, non-experimental design and a qualitative approach will be used, in addition to the presence of documentary and field research. Obtaining as such a research sample of 25 students and 1 teacher, where an interview with the classroom teacher and direct observation of the students will be used as part of the research techniques. The results show that there are children who have not developed their socio-affective skills correctly, indicating that they do not interact with other classmates regardless of their abilities. It is concluded that it is important to promote educational inclusion within the classroom, since it allows students to respect and be empathetic with classmates with associated and non-associated special educational needs.